Penyuluhan Dampak Positif dan Negatif Media Sosial Terhadap Kalangan Remaja Di Desa Way Heling Kecamatan Lengkiti Kabupaten Ogan Komering Ulu - Desti Arini (Abdimas Universal, 2020)
Starting from the work program of KKN Baturaja University students who asked lecturers from the Faculty of Engineering and Computers to conduct counseling with the theme "Appropriate Technology" in Way Heling Village, Lengkiti District, Ogan Komering Ulu Regency. This extension activity was aimed at youth cadets in Way Heling Village, where the purpose of community service conducted by the Faculty of Engineering and Computers at Baturaja University is to open up insights on social media and the distribution of information produced by social media in the digital age, to be selective, wise and critical in accessing and / or spreading information in the media social. The method of implementing activities in the form of counseling, discussion, question and answer and participants is youth youths added by the village helicopter Way Way. The results of the counseling showed that the teenagers were interested in creating social media in the economic, education and social culture field to improve their life expectancy and even they expected their village to be selected as a target village in terms of information and communication (information village). The conclusions that could be drawn from this extension activity showed a response positive and very good addressed by participants to the instructor.